San Juanito y la Postura en niños del segundo año de educación general básica. - Elizalde Rivera, Richar Enrique (2025)
This research was carried out with the objective of determining the effectiveness of the San Juanito dance on body posture in children in the second year of basic general education. The methodology was based on a quantitative approach study, with a field correlational design. The analysis of the results obtained from the observation shows that, the posture of the children, it is detected that, although the majority of the students maintain a correct posture, a small percentage presents inappropriate postures when sitting, with an average of negative responses from the 6% to 16%. This indicates the need to reinforce postural education, especially in children who show incorrect postures, to avoid future problems, such as spinal disorders or lumbar pain. The importance of continuing to implement corrective measures to prevent injuries and promote appropriate postural habits during the process of physical development of students is highlighted. The proposal presented seeks to strengthen awareness and improve body posture in students through the implementation of educational strategies that integrate physical activities and postural correctives. It is proposed to use dynamic methods, such as songs and dance, to promote correct posture in daily activities, both inside and outside the classroom. After applying the McNemar test, it was determined that the p value is less than 0.05, so the null hypothesis is discarded and the alternative is adopted, which maintains that the San Juanito dance is effective in posture. body of children in the second year of general basic education.